Growth kinetics study and process optimization of lactic acid fermentation in laboratory scale fermenter - Mel, Maizirwan; Abdul Karim, Mohamed Ismail; Jamal, Parveen; Mohamed Salleh, Mohamad Ramlan; Zakaria, Ruzi Aini (2005)
The purpose of this research was to study the growth kinetics of Lactobacillus rhamnosus in laboratory scale fermenter and to optimize the production of lactic acid with varying certain operating conditions of fermenter. The experiment was designed by Taguchi Method using STATISTICA software to improve the process quality and to increase the lactic acid production. Three parameters have been chosen to be main parameters that effect significantly to L. rhamnosus growth that were agitation speed of the impeller, dissolve oxygen level (pO2) and pH. From comparison between the four runs, the best production of lactic acid has been achieved at lower agitation rate (cascade control, 1-500 rpm), slightly lower pO2 level (10%), and lower pH level (pH 6) with lactic acid concentration of 14.55 g/L. The maximum growth rate and productivity have been obtained at 0.5 h-1 and 0.1282 g/g.h., respectively.